An Evaluation of the Utilization of Special Allocation Funds in the Field of Vocational Secondary Education - Hermansyah,; Soenarto,; Sukardi, (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to provide information on how well the utilization of special allocation funds (DAK) in vocational secondary education in terms of the context, input, process, and product components.This study is an evaluation study using the research model of CIPP (context, input, process, product) developed by Stufflebeam. The sample consists of 181 respondents from five vocational high schools of national priority. The data were collected using questionnaires and through observations, interviews, and documentation. The instrument validation uses expert judgment, Aiken v index, and the product-moment correlation test for the questionnaire. The reliability testing uses the Alpha Cronbach formula. Data were analyzed using quantitative descriptive analysis methods.The results of the study show that the utilization of DAK in the vocational secondary education sector of the components of: (1) context, describing the utilization of DAK in the vocational secondary education sector in:(a) 10 SMKN Padang in the excellent category with a percentage of 95%; (b) State Vocational School in Padang in a very good category with a percentage of 95.7%; (c) SMKN 2 Sawahlunto in the very good category with a percentage of 67.4%; (d) SMK 9 Padang in the excellent category with a percentage of 52.5%; (e) SMK 4 Padang in the excellent category with a percentage of 65.3%; 2) inputs: (a) SMK 10 Padang in the excellent category with a percentage of 45%; PP Negeri Padang State Vocational School in the excellent category with a percentage of 82.5%; (c) SMKN 2 Sawahlunto in the very good category with a percentage of 52.3%; (d) SMK 9 Padang in the excellent category with a percentage of 42.5%; (e) SMK 4 Padang in the excellent category with a percentage of 44.1%; 3) process: a) SMK 10 Padang in the good category with a percentage of 50%; (b) State Vocational School in Padang in the very good category with a percentage of 86.9%; (c) SMKN 2 Sawahlunto in the very good category with a percentage of 47.8%; (d) SMK 9 Padang in the excellent category with a percentage of 40%; (e) SMK 4 Padang in the good category with a percentage of 50%; 4) product: (a) 10 SMKN Padang in the good category with a percentage of 50%; (b) State Vocational School in Padang in the very good category with a percentage of 47.7%; (c) SMKN 2 Sawahlunto in the good category with a percentage of 54.3%; (d) SMK 9 Padang in the excellent category with a percentage of 32.5%; (e) SMK 4 Padang in the good category with a percentage of 44.1%.